Path analysis using the theory of planned behavior on taking blood supplement tablets and eating nutritious food - Laferani, Yuni; Surtimanah, Tuti; Sjamsuddin, Irfan Nafis (Universitas Gadjah Mada, 2025)
Purpose: This study investigates the direct and indirect effects of knowledge, intention, and behavior related to drinking Blood Supplement Tablets and Eating Nutritious food, guided by the Theory of Planned Behavior, following education through video and comic media. Methods: This study employs a quantitative approach using a quasi-experimental pre-post test two-group design. The sample size consists of 63 people, and the sampling technique employed is stratified sampling. Results: The direct effect of knowledge on actual behavior is -0.036, while the indirect effect is 0.006. The direct effect of attitude on actual behavior is 0.216, and the indirect effect is 0.027. Subjective norms have a greater indirect effect value of 0.035 compared to the direct effect value (-0.125). The same thing happens for the actual control variable, which has a direct effect value of 0.135 while the indirect effect is 0.052. The intention variable has a direct effect of 0.210 on actual behavior. Conclusion: Research shows that attitudes and intentions have a direct impact on healthy behavior, while knowledge, subjective norms, and behavioral control do not have a direct effect. These findings can serve as the basis for health education interventions, with suggestions for incorporating other behavioral models and exploring more diverse subjects.